Implementation of Android Application-Based Learning Media on Motorcycle Electrical Maintenance Materials in Vocational High Schools - Sigit Purnomo; Tri Pamungkas; Arif Bintoro Johan; Elyas Djufri (Universitas Sultan Ageng Tirtayasa, 2023)
Purpose of this study was to produce learning media and test the feasibility of learning media based on android applications at Vocational High Schools. The type of research used in this research is implementation research. The subjects in the study were 31 students of class XI TBSM Vocational High Schools. The data collection instrument used quantitative descriptive analysis to determine the feasibility of learning media. The results of this study indicate: (1) Development research produces learning media for motorcycle electrical maintenance materials for students of class XI TBSM with the development process through the following stages: (2) Android-based learning media is categorized as feasible to use in learning to get validation results from Experimental class of 87.5%, Control class 78.5%, So it can be concluded that learning with Android is more effective for students.